Zarządzanie wiedzą a wprowadzanie zmian w organizacji - Tabaszewska, Edyta (Knowledge management and bringing changes into organization, 2006)
The aim of the paper is to present the role of knowledge management in the rationalization process of bringing changes into organization. In author's opinion the knowledge management can fulfill two functions within such process. Firstly, the realization of processes of knowledge management causes, that changes are really important for an organization and the process of bringing them is properly supervised. Secondly it is possible to manage the knowledge about changes, and therefore reach greater effectiveness of subsequent changes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 406-412